Oxylator and SCUBA dive regulators: useful utilities for in-water resuscitation. Issue 7 (16th July 2012) - Winkler, Bernd E; Froeba, Gebhard; Koch, Andreas; Kaehler, Wataru; Muth, Claus-Martin
Abstract : Introduction: In water resuscitation has been reported to enhance the outcome of drowning victims. Mouth-to-mouth ventilation during swimming is challenging. Therefore, the efficacy of ventilation utilities was evaluated. Methods: Ventilation was assessed with the Oxylator ventilator, as well as the consecutive self-contained underwater breathing apparatus (SCUBA) regulators using an anaesthetic test lung: Poseidon Cyklon 5000, Poseidon XStream, Apeks TX 100, Spiro Arctic, Scubapro Air2 and Buddy AutoAir. Results: Oxylator, Apeks TX 100, Arctic and Buddy AutoAir delivered reliable peak pressures and tidal volumes. In contrast, the ventilation parameters remarkably depended on duration and depth of pressing the purge button in Poseidon Cyklon 5000, Poseidon XStream and Scubapro Air2. Critical peak pressures occurred during ventilation with all these three regulators. Discussion: The use of Poseidon Cyklon 5000, Poseidon XStream and Scubapro Air2 regulators is consequently not recommended for in-water ventilation. With the limitation that the devices were tested with a test lung and not in a human field study, Apeks TX 100, Spiro Arctic and Buddy AutoAir might be used for emergency ventilation and probably ease in-water resuscitation for the dive buddy of the victim. Professional rescue divers could be equipped with the Oxylator and an oxygen tank to achieve an early onset of efficient in-water ventilation in drowning victims.